Glycemic variability and mortality in patients with aortic diseases: A multicenter retrospective cohort study - Shanshan Tang; Zhiqiang Zhang; Yu Cheng; Lizhuang Zhang; Qiyao Wang; Cuihua Wang (PLoS ONE, 2025)
Background The influence of glycemic variability (GV), defined as blood glucose fluctuations, on short-term mortality in patients with aortic diseases, such as aneurysms and dissections, remains understudied. This study evaluates the association between GV and mortality, explores non-linear patterns, and determines a GV threshold predictive of mortality risk. Methods A retrospective analysis of 2,441 patients with aortic aneurysm or dissection from the MIMIC IV and eICU-CRD databases was performed. Key variables, including demographics, clinical characteristics, comorbidities, laboratory findings, and treatments, were assessed. Logistic and Cox regression models, smooth curve fitting, and subgroup analyses examined associations between GV and ICU and 30-day mortality. Results ICU mortality occurred in 165 patients (6.8%), and 30-day mortality in 235 patients (9.6%). Increased GV was linearly associated with ICU mortality risk (P for non-linearity = 0.666). For 30-day mortality, a U-shaped relationship was observed, with minimal risk at a GV index of 0.2047 (P for non-linearity = 0.041). Adjusted models confirmed these findings (ICU mortality: OR = 1.15, 95% CI = 1.03–1.30, 30-day mortality: HR = 1.10, 95% CI = 1.03–1.18). Conclusions GV is significantly associated with short-term mortality in aortic disease patients, with a U-shaped pattern for 30-day mortality and an optimal threshold of 0.2047. These findings underscore the importance of tailored glucose management strategies and call for further research into underlying mechanisms.